PERANAN CAHAYA PEREMPUAN WOMEN’S CRISIS CENTRE (WCC) BENGKULU DALAM MENANGANI KASUS KDRT PERSPEKTIF HUKUM ISLAM DAN UU NO. 23 TAHUN 2004 TENTANG PENGHAPUSAN KDRT - Eli Rahmidiani (Universitas Islam Negeri Fatmawati Sukarno, 2018)
The purpose of this study is to find out how the role of women’s women’s crisis center Bengkulu in handling cases of domestic violence in the perspective of Islamic Law and Law Number twenty three Year two four About Aboli- tion of Domestic Violence. This type of research is field research (field research) supported by library research (library research). From the result of this research, it is concluded that the role of women’s crisis center Bengkulu women in handling cases of domestic violence in collaboration with legal aid institutions, medical, police, and courts, this co- operation is called case-handling network in an effort to reach cases of domestic violence and sexual violence can be handled and facilitated by victims such as safe houses, counseling rooms, to share stories and facilities in the form of legal assistance and handling in a familial manner while reducing the number of sexual violence handled by prevention programs. Analysis of Islamic law against domestic violence that in Al-Qur’an Surah An-Nisa ‘verse thirty-four explains that a husband should not immediately hurt his wife with a painful blow. Since Islam does not teach such a thing, there have been good and right rules when the husband is facing such problems. Although beating the wife is justified in Is- lam, it is hitting that does not hurt the wife and with educational intentions. Analysis of Law Number Twenty-three Years Two Thousand Four About Abolition of Domestic Violence is able to avoid family violence, when disharmony occurs between husband and wife. More broadly, it is necessary to have fundamental changes in women’s status and attitudes toward both women and men in society, the need for continuous and strategic efforts to deconstruct traditional power structures that have been considered legitimate and deconstruct cultural assumptions and religions that strengthen and legitimize violence